Impacts of yarn twist and staple length on UV protection of plain-knitted cotton fabrics. Issue 12 (1st December 2016) - Wong, Wai-Yin; Lam, Jimmy Kwok-Cheong; Kan, Chi-Wai; Postle, Ronald
Abstract : Yarn construction is an important attribute in knitting and end use performance of knitwear. Holistically, yarn construction affects fabric thickness and weight, and thereby influences ultraviolet (UV) protection of fabrics. Although impact of yarn construction on UV protection of fabrics is apparent, there appears to be limited research on it. This paper studied the UV protection of plain-knitted fabrics made of three types of ring-spun cotton yarns varying in yarn twist level and staple length. The results show that these yarn properties affect UV protection of fabrics differently before and after laundering. The modified low-twisted yarn possesses a bulky feature which creates a porous fabric structure for more ultraviolet radiation (UVR) transmission. The extra-long staple yarn offers uniform fabric appearance for higher UVR reflection. However, the regularity of yarn also restricts the fabric shrinkage in laundering and thus improvement in UV protection by shrinkage is not as obvious as that provided by the conventional short-staple yarn.